Axially wrinkled tubular SnO2/TiO2 heterostructures for effective degradation of organic pollutants. (December 2022) - Huang, Honglan; Zhao, Shengzhe; Yang, Yi; Wang, Yan; Lu, Ran; Lu, Yun; Chen, Jinju
Abstract: Axially wrinkled SnO2 /TiO2 heteronanotubes have been successfully prepared by sacrificial template method combined with hydrothermal synthesis. The special folded morphology of SnO2 /TiO2 nanostructures may provide more active sites, and the S-scheme heterojunction between SnO2 and TiO2 enhances the separation of photogenerated electron-hole pairs, which are conducive to the improvement of photocatalytic degradation for organic pollutants. Using SnO2 /TiO2 nanotubes as catalyst, the removal rate of Rhodamine B (RhB), methyl orange (MO) and tetracycline hydrochloride (TCH) under the irradiation of a xenon lamp is 93%, 91% and 85%, respectively. After five cycles, the removal efficiency of organic pollutants maintains almost unchanged, indicating that the synthesized SnO2 /TiO2 nanotubes has good stability and reusability. In addition, trapping experiments have been carried out to investigate the major reactive oxidative species for organic pollutants photodegradation. This study provides a facile avenue to design nanotublar photocatalysts with enhanced degradation performance for organic pollutants.